Thinking through Confucian modernity : a study of Mou Zongsan's moral metaphysics - Billioud, Sébastien (BRILL, 2011)
This book explores a pivotal dimension of Mou Zongsan's philosophy--that is, his project of reconstructing a moral metaphysics based largely on a dialogue between reinterpreted Chinese thought and Kantism--and thoroughly analyzes a number of his most paradigmatic concepts.